Application of C-banding in two Arachis wild species, Arachis pintoi Krapov. and W.C. Gregory and A-villosulicarpa Hoehne to mitotic chromosome analyses - Pierozzi, Neiva I.; Galgaro, M. Letícia [UNESP]; Lopes, Catalina R. [UNESP] (Univ Florence Botany Inst, 2001)
Two wild diploid (2n = 20 chromosomes) and self-pollinating Arachis species, Arachis Pintoi Krapov and W.C.Gregory and A. villosulicarpa Hoehne were submmited to C-band technique to karyotype analyses. Root tips were employed in the analyses. Morphometric data chose that chromosome lengths varied from 3.12 in A. villosulicarpa to 1.45 in A. Pintoi. Karyotype formula obtained was 10sm to A. Pintoi and 9sm + 1m to A. villosulicarpa. There was a predominance of pericentromeric C-band in all mitotic metaphasic chromosomes in both species. Besides C-band values, both species still did not differ in respect to chromosome absolute and relative lengths, centromeric index, symmetry index and total karyotype haploid length. C-band and morphometric data did not show strong or significant differences which could separate these two species of peanut which belong to evolutive different sections.
Keywords: Arachis; C-band; Mitotic chromosomes